Diagnosis and treatment of depression according to the functional recovery paradigm - G. M. Usov (Неврология, нейропсихиатрия, психосоматика)
Since the appearance of the first antidepressants, ideas about the goals of long-term treatment of depression have changed considerably. The prevailing priority in the 1960s to 1980s of relieving current depressive symptoms and ending the current episode – shifted to achieving remission in the early 1990s and functional recovery in the mid-2010s. The general recognition of a new approach to the treatment of depression is reflected in the inclusion of functional disorder in the ICD-11 diagnostic criteria for a depressive episode. The paradigm shift in therapy has been driven by advances in the field of psychopharmacology that have led to the development of antidepressants with a fundamentally new mechanism of action that provides a broader therapeutic effect combined with a more favorable tolerability profile. Agomelatine provides a harmonious and complete reduction of depression symptoms, including those resistant to other antidepressants, and a stable clinical and functional remission of high quality, i.e., it allows the achievement of all three therapeutic goals.